Separação cega de sinais de fala utilizando detectores de voz. - Rocha, Ronaldo Alencar da (2014)
In this work we contemplate the use of voice detectors as a preprocessing step of a time-domain blind source separation technique, employing second order statistics in the separation of convolutive and determined mixtures. This algorithm is adapted to perform the separation both in fullband and in subbands, considering the presence and the absence of a moments of silence in mixtures of voice signals. The main idea aims at detect portions of the mixtures containing voice activity, avoiding that the separation algorithm is triggered in the absence of voice, promoting performance improvement and reduced computational cost.